Modern Organisations and Fayolism - T., Senthil Kumar (Global Business and Social Entrepreneurship Resources, 2016)
Henri Fayol is widely considered to be the father of administrative management theory which focussed on the development of broad administrative principles that were applicable to general and higher managerial levels. Though his contribution to the field of management sciences is indispensable, it is argued that some of the fourteen principles propounded by him are rather outmoded due to the way the present-day organisations conduct their business.